Characterization of Natural Bioactive Compounds from Greek Oregano Accessions Subjected to Advanced Extraction Techniques - Christina Panagiotidou; Elisavet Bouloumpasi; Maria Irakli; Paschalina Chatzopoulou (Plants)
Nowadays, eco-friendly extraction techniques are often used to develop natural plant extracts for commercial use. In the current investigation, Greek oregano (Origanum vulgare) phenolic extracts from different cultivated accessions were recovered employing ultrasonic-assisted extraction (UAE), microwave-assisted extraction (MAE), and accelerated solvent extraction (ASE). The phytochemical profile of the oregano extracts, as determined by spectrophotometric and chromatographic techniques, as well as antioxidant activity (ABTS, DPPH, and FRAP assays), was used to compare the three extraction approaches. The results showed that oregano phenolic extracts obtained by MAE held the highest total phenolic content, total flavonoid content, and also a higher content of the main phenolic compounds identified, rosmarinic acid, salvianolic acid B and carvacrol, as determined by LC-MS analysis, followed by those extracted by UAE and ASE. All of the tested extracts exhibited relatively high antioxidant activities, especially the MAE extracts. Oregano extracts produced by various extraction techniques were subjected to a multivariate data analysis to highlight differences in phytochemical profiles, and their correlation to antioxidant activity. According to our findings, it was evident that MAE offers more efficient and effective extraction of bioactive compounds in terms of obtaining phytochemical-rich oregano extracts, with applications in the food and pharmaceutical industries.